The Effect of RAFT Strategy Assisted by Graphic Images on the Students’ Achievement in Writing - Muhammad Ikhsan Ahmadi Tanjung (Randwick International of Education and Linguistics Science Journal, 2023)
The objective of this research was to find out the significant effect of RAFT strategy assisted by graphic images on the students’ achievement in writing. The Research used in this study was an experimental research. This research design was conducted at SMA Al-ULUM Medan, located on Jalan Tuasan No.35, Kecamatan Medan Tembung. The population of this research was the classes at eleven grade in academic year 2016/2017, which consisted of 2 classes, 51 students. The researcher took two classes by using total random sampling, XI-IPS was as the control class that consisted of 22 students and XI IPA was as the experimental class which involved 29 students. Each class was given a pre-test, treatment, and post-test. The control class was taught by using lecture method, while the experimental class was treated by using RAFT strategy. The instrument of this research was written test. The data were analyzed by using t-test formula. Then, the result showed that the students taught using by using RAFT Strategy got the higher score than those taught by using lecture method. In conclusion, there was the significant effect on the students’ achievement in writing by using RAFT Strategy Assisted by Graphic Images